Powstanie rządu Prawa i Sprawiedliwości, Ligi Polskich Rodzin i Samoobrony jako elementu budowy IV RP – analiza prasoznawcza wybranych dzienników ogólnopolskich - Kuca, Paweł (Polityka i Społeczeństwo, 2020)
The main purpose of the article is to present and analyse press studies which concern the coming into existence of the government coalition and the period of collaborative government by the Law and Justice (Prawo i Sprawiedliwość), The Polish Family League (Liga Polskich Rodzin) and Self-Defence (Samoobrona) in 2006. It is the latest contribution to examinations related to press studies which concern the structure of the so-called IV Republic, the political project carried out in Poland in the years 2005–2007. Examinations included the analysis about the attitudes of the media to the construction of the IV Republic. The described analysis in the present article concerns three daily newspapers “Gazeta Wyborcza”, “Rzeczpospolita” and “Nasz Dziennik”. Examinations were conducted based on an analysis of the contents of the press.